Elementary reduction of matrices over Bezout ring with stable range 1 (in Ukrainian) - O. M. Romaniv (Математичні Студії, 2012)
We prove that a commutative Bezout ring with stable range 1 is a ring with elementary reduction of matrices and that every singular matrice over commutative Bezout ring with stable range 1 is products of idempotent matrices.